Hiccups leading to dipnoea in a patient with Covid-19 - Holanda, Plínio de Oliveira; Nascimento, José Carlos Rodrigue; Salmito, Francisco Thiago; Nogueira, Ingrid Correia (Brazilian Journal of Case Reports, 2022)
In 2020 and 2021, the Covid-19 pandemic caused drastic consequences around the world. The disease causes a flu syndrome with clinical pictures ranging from mild to severe. Since it is a systemic flu syndrome, several clinical manifestations have been described for this disease, but cases of hiccups associated with Covid-19 have rarely been reported. This report describes a rare case presented in which a patient with Covid-19 developed respiratory discomfort after complaining of persistent hiccups. The patient was treated clinically and experienced a sudden improvement in their dyspnoea immediately after the disappearance of the hiccups crisis. This sudden improvement suggests a very likely cause–effect relationship.